Soil Moisture from Metop ASCAT Data at High Latitudes - Bartsch, Annett; Melzer, Thomas; Elger, Kirsten; Heim, Birgit (The Northern Publisher, 2012)
Several global satellite-derived soil moisture datasets exist to date. They are based on analyses of passive or active microwave data. Resolution is coarse at 25 km, but temporal sampling is very high. A monitoring service for applications at high latitudes is implemented within the European Space Agency (ESA) data User Element (DUE) initiative ‘Permafrost.’ Measurements are based on Metop ASCAT, a European active microwave instrument (scatterometer, C-band). This study discusses comparisons between these data and in situ measurements from Alaska. Weekly averaged values have been compared to soil moisture records at several USDA stations. Results show that in situ soil moisture measurements at shallow depths reflect variations of satellite-derived relative near-surface soil moisture although the used sensor provides data at only 25 km resolution. There are indications that this relationship is impacted by micro-topography and temporal offsets related to snowmelt and active layer dynamics.